Expression and Transformation of Loyalty in a Contractual Service Setting: A Processual View. Issue 2 (May 2019) - Quach, Sara; Hewege, Chandana; Le, Viet
The main objectives of this study are twofold: (1) to gauge the expressions of loyalty toward a service provider, (2) to identify possible transformations of loyalty in the contractual service settings. Using an integrative theoretical perspective, the study presents a more holistic understanding of the dynamics of loyalty transformation taking a processual view. Following an interpretive research approach, we conducted twenty-eight semi-structured interviews with customers and managers of major mobile telephony service providers. The findings confirm that customer loyalty can transform into various states: (1) fanaticism, (2) stage of transition, (3) point of disinterest, and (4) state of betrayal. Moreover, it is determined that customers could express their loyalty to the service provider in several ways signifying their concern, advocacy, rituals, identification, beliefs, and nostalgic feelings.